Hubungan Konsep Diri terhadap Kepercayaan Diri Siswa Kelas XII SMA Teuku Umar Semarang - Ariyani, Selgi Mei; Handayani, Arri; Setiawan, Agus (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2023)
Research on the Relationship between Self-Concept and Self-Confidence in Class XII Students of Teuku Umar High School, Semarang motivated by the lack of self-confidence of class XII students, this is indicated by the results of the AKPD (Students Needs Questionnaire) many students still chose the item "I lack self-confidence" which received a percentage of 3.26% in the high category.The aim of this research is to find out whether there is a relationship between self-concept and the self-confidence of class XII students at SMA Teuku Umar Semarang. In this research, the method used was quantitative with correlation research type, the population in this research was 142 students. This research sample took 75% of the population so that the sample used was 106 students which was determined using a saturated sampling technique.Based on the Pearson product moment correlation test, the calculated r value is 0.467, while the r table for a sample size of 106 is 0.160. Therefore, 0.467 > 0.160, it can be concluded that there is a significant relationship between self-concept and the self-confidence of class XII students at SMA Teuku Umar Semarang.This relationship shows a positive direction, because the calculated r value obtained in this study is positive. A positive relationship means that if self-concept is high then self-confidence is high, and vice versa if self-concept is low then self-confidence is low.Keywords: student, self concept, self confidence